2021
DOI: 10.3847/psj/abf92d
|View full text |Cite
|
Sign up to set email alerts
|

Titan in Transit: Ultraviolet Stellar Occultation Observations Reveal a Complex Atmospheric Structure

Abstract: Transit spectroscopy is a key tool for exoplanet atmospheric characterization. However, transit spectrum observations can be limited by aerosol extinction when gas opacities are weak. The ultraviolet wavelength range contains a variety of strong molecular and atomic features, potentially enabling gas species detection even when atmospheric hazes are present. To understand the interplay between aerosol extinction and ultraviolet molecular opacities, we investigate transmission through the atmosphere of Saturn’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Heng & Li (2021) used high-quality phase curves of Jupiter from the Cassini Imaging Science Subsystem (Porco et al 2004;Li et al 2018) to infer properties of Jovian clouds with potential implications for JWST. Finally, Tribbett et al (2021) performed retrievals on effective transit spectra of Titan-generated from stellar occultations observed by the Cassini Ultraviolet Imaging Spectrograph (Esposito et al 2004;Koskinen et al 2011)-and showed that simple parameterizations of haze extinction failed to detect the presence of known haze layers/overdensities.…”
Section: Introductionmentioning
confidence: 99%
“…Heng & Li (2021) used high-quality phase curves of Jupiter from the Cassini Imaging Science Subsystem (Porco et al 2004;Li et al 2018) to infer properties of Jovian clouds with potential implications for JWST. Finally, Tribbett et al (2021) performed retrievals on effective transit spectra of Titan-generated from stellar occultations observed by the Cassini Ultraviolet Imaging Spectrograph (Esposito et al 2004;Koskinen et al 2011)-and showed that simple parameterizations of haze extinction failed to detect the presence of known haze layers/overdensities.…”
Section: Introductionmentioning
confidence: 99%
“…Heng & Li (2021) used high-quality phase curves of Jupiter from the Cassini Imaging Science Subsystem (Porco et al 2004;Li et al 2018) to infer properties of Jovian clouds with potential implications for JWST. Finally, Tribbett et al (2021) performed retrievals on effective transit spectra of Titangenerated from stellar occultations observed by the Cassini Ultraviolet Imaging Spectrograph (Esposito et al 2004;Koskinen et al 2011) -and showed that simple parameterizations of haze extinction failed to detect the presence of known haze layers/over-densities.…”
Section: Introductionmentioning
confidence: 99%
“…Whole-disk observations of solar system worlds provide a unique bridge between solar system planetary science and exoplanetary science (Kane et al 2021). Not only do these data transform well-proven instrumentation for solar system remote sensing into new vehicles for exoplanet exploration, but the resulting data sets can prove crucial in validating approaches to exoplanet characterization (Marley et al 2014;Lupu et al 2016;Mayorga et al 2016;Heng & Li 2021;Tribbett et al 2021;Robinson & Salvador 2022). Foremost among solar system targets for exoplanet analog observations is Earth-the only known inhabited world and the archetypal habitable planet that would be characterized by under-development space telescope missions (Gaudi et al 2018;Quanz et al 2018;Roberge & Moustakas 2018), including the recently dubbed "Habitable Worlds Observatory" recommended by the Decadal Survey on Astronomy and Astrophysics for the 2020s (National Academies of Science, Engineering, and Medicine 2023).…”
Section: Introductionmentioning
confidence: 99%